Legal Construction of Criminal Prosecution Against Perpetrators of Rape in the Metaverse - Muhammad Firkan Muhammad Muslim; indi Izza Afdania (Perantara Law Review, 2024)
Virtual rape was experienced by a girl under 16 years old who was exploring the Metaverse world, but her avatar was raped by several other avatars. This girl had no physical injuries but experienced psychological and emotional trauma similar to rape victims in the real world. This case is a challenge in itself in the legal world, considering the many limitations of cybercrime cases in terms of protection, accountability, and punishment. This research uses normative research methods with a statutory approach, a conceptual approach, and a case approach. According to positive law in Indonesia, there is no law that regulates elements of online sexual violence. This is a proof that there are limited protections for virtual rape victims. There are two views as a solution to these cases in the Metaverse, namely (1) the avatar in the Metaverse is considered a separate legal personality, which means that it is seen as a different entity. (2) Avatars are seen as legal subjects that cannot be separated from the conventional world by using the concept of vicarious liability.